Treatment of biodigested coffee processing wastewater using Fenton's oxidation and coagulation/flocculation - Gomes de Barros, Valciney [UNESP] (2020)
Biodigested coffee processing wastewater (CPW) presents a high organic load and does not meet the limits imposed by legislation (namely in Brazil) for discharge into water bodies. Anaerobic digestion generally cannot provide a satisfactory organic matter reduction in CPW as a significant fraction of recalcitrant compounds still persists in the treated effluent. So, this study aims to find alternative ways to remove refractory organic compounds from this wastewater in order to improve the biodegradability and reduce the toxicity, which will allow its recirculation back into the anaerobic digester. Three treatment approaches (Fenton's oxidation - Approach 1, Coagulation/flocculation (C/F) - Approach 2, and the combination of C/F with Fenton's process - Approach 3) were selected to be applied to the biodigested CPW in order to achieve that objective. The application of the Fenton process under the optimal operating conditions (initial pH = 5.0; T = 55 °C, [Fe3+] = 1.8 g L−1 and [H2O2] = 9.0 g L−1) increased the biodegradability (the BOD5:COD ratio raised from 0.34 ± 0.02 in biodigested CPW to 0.44 ± 0.01 after treatment) and eliminated the toxicity (0.0% of Vibrio fischeri inhibition) along with moderate removals of organic matter (51.3%, 55.7% and 39.7% for total organic carbon – TOC, chemical oxygen demand – COD and biochemical oxygen demand - BOD5, respectively). The implementation of a coagulation/flocculation process upstream from Fenton's oxidation, under the best operating conditions (pH 10–11 and [Fe3+] = 250 mg L−1), also allowed to slightly increase the biodegradability (from 0.34 to 0.47) and reduce the toxicity, whereas providing a higher removal of organic matter (TOC = 76.2%, COD = 76.5 and BOD5 = 66.3% for both processes together). Approach 1 and Approach 3 showed to be the best ones, implying similar operating costs (∼74 R$ m−3/∼17 € m−3) and constitute an attractive option for managing biodigested CPW.